Ruins of the past: the use and perception of abandoned structures in the Maya lowlands - Stanton, Travis W., author; Magnoni, Aline, author; Stanton, Travis W., editor; Magnoni, Aline, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2008)
From the Formative to the present, Maya peoples have continuously built, altered, abandoned, and re-used structures, imbuing them with new meanings at each transformation. Ruins of the Past is the first volume to focus on how previously built structures in the Maya Lowlands were used and perceived by later peoples, exploring the topic through concepts of landscape, place, and memory.--Book jacket.
Foreword / Wendy Ashmore -- Places of remembrance: the use and perception of abandoned structures in the Maya lowlands / Travis W. Stanton and Aline Magnoni -- Forgotten structures, haunted houses, and occupied hearts: ancient perspectives and contemporary interpretations of abandoned sites and buildings in the Mirador Basin, Guatemala / Richard D. Hansen, Wayne K. Howell, and Stanley P. Guenter -- The transformation of abandoned architecture at Piedras Negras / Mark B. Child and Charles W. Golden -- Structure abandonment and landscape transformation: examples from the Three Rivers region / Lauren A. Sullivan [and others] -- Manipulating memory in the wake of dynastic decline at El Perú-Waka': termination deposits at abandoned structure M13-1 / Olivia C. Navarro Farr, David A. Freidel, and Ana Lucía Arroyave Prera -- Establishing and reusing sacred place: a diachronic perspective from Blackman Eddy, Belize / M. Kathryn Brown and James F. Garber -- Anatomy of a post-collapse society: identity and interaction in early postclassic Copán / T. Kam Manahan -- Landscape transformations and changing perceptions at Chunchucmil, Yucatán / Aline Magnoni, Scott R. Hutson, and Travis W. Stanton -- Edzná: a lived place through time / Antonio Benavides C. -- Memories, meanings, and historical awareness: post-abandonment behaviors among the lowland Maya / Marcello A. Canuto and Anthony P. Andrews -- Afterword / Denise Fay Brown.
Keywords: Maya architecture; Abandoned buildings -- Mexico; Abandoned buildings -- Central America; Buildings -- Remodeling for other use -- Mexico; Buildings -- Remodeling for other use -- Central America; Mexico -- Antiquities; Central America -- Antiquities